2014
DOI: 10.35799/jis.14.2.2014.5927
|View full text |Cite
|
Sign up to set email alerts
|

PREDIKSI HARGA SAHAM PT. BRI, Tbk. MENGGUNAKAN METODE ARIMA (Autoregressive Integrated Moving Average)

Abstract: PREDIKSI HARGA SAHAM PT. BRI, Tbk. MENGGUNAKAN METODE ARIMA (Autoregressive Integrated Moving Average) Greis S. Lilipaly1) , Djoni Hatidja1) , John S. Kekenusa1) ABSTRAK Metode ARIMA adalah salah satu metode yang dapat digunakan dalam memprediksi perubahan harga saham. Tujuan dari penelitian ini adalah untuk membuat model ARIMA dan memprediksi harga saham PT. BRI, Tbk. bulan November 2014. Penelitian menggunakan data harga saham  harian  maksimum dan minimum PT. BRI, Tbk. Data yang digunakan yaitu data sekunde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
7
0
4
Order By: Relevance
“…It also can be concluded that ARIMA (1,1,1) able to forecast the daily closing price indices for ISSI successfully and accurately. This result is consistent with previous research conducted by Ashik and Kannan (2017), Ayo (2014), Lilipaly et al, (2014), Mondal et al, (2014) and Devi, Sundar, and Alli (2013).…”
Section: Resultssupporting
confidence: 94%
“…It also can be concluded that ARIMA (1,1,1) able to forecast the daily closing price indices for ISSI successfully and accurately. This result is consistent with previous research conducted by Ashik and Kannan (2017), Ayo (2014), Lilipaly et al, (2014), Mondal et al, (2014) and Devi, Sundar, and Alli (2013).…”
Section: Resultssupporting
confidence: 94%
“…The best model was shown by the forecasting of Nifty 50 stock price, with an error percentage of 16.26%. Lilipaly et al (2014), in his research predicting the stock price of Bank Rakyat Indonesia Tbk by using daily stock data from 2011 to October 2014, showed that the ARIMA model is suitable and can be used to predict stock prices in November 2014. ARIMA model suitable for the maximum stock price is ARIMA (2,1,3) and ARIMA (2,1,3) is suitable for the minimum stock price.…”
Section: B Theoretical Background 1 Technical Analysismentioning
confidence: 99%
“…Prediksi adalah proses memperkirakan secara sistematis tentang sesuatu yang mungkin terjadi di masa depan berdasarkan informasi masa lalu dan sekarang yang dimiliki, agar kesalahannya dapat diperkecil. Prediksi tidak harus memberikan jawaban secara pasti suatu kejadian yang akan terjadi, melainkan berusaha untuk mencari jawaban sedekat mungkin yang akan terjadi [5].…”
Section: Model Time Seriesunclassified